Effectiveness of non-steroidal anti-inflammatory drugs as host modulation on periodontitis healing: Efektivitas non-steroid anti-inflammatory drugs sebagai host modulation terhadap penyembuhan periodontitis - Thahir, Hasanuddin; Ibriana; Djais, Arni Irawaty (Makassar Dental Journal, 2024)
To describe the effectiveness of non-steroidal anti-inflammatory drugs (NSAIDs) as host modulation on the healing of periodon-titis based on existing literature. The literature search was conducted independently, including articles in PubMed with full text and written in English using the keywords periodontal disease AND periodontitis AND host modulation AND nonsteroidal anti-inflammatory drugs OR NSAIDs. As a result, periodontitis is no longer defined as a disease caused by bacteria alone, but is now seen as an uncontrolled disease related to the immune response caused by dysbiosis. NSAIDs are one of the host mo-dulation agents that have been investigated for their effectiveness in healing periodontal disease. Some articles support that the combination of NSAIDs and scaling root planing (SRP) can treat periodontitis, but there is some literature that states that this is not the case when compared to conventional treatments. It was concluded that NSAIDs are effective as host modulation for periodontitis healing significantly on clinical parameter measurements such as plaque index reduction, probing depth, bleeding on probing, gingival index, and clinical attachment level improvement compared to SRP combined with placebo.